Centrosome defects cause microcephaly by activating the 53BP1‐USP28‐TP53 mitotic surveillance pathway. (23rd November 2020) - Phan, Thao P; Maryniak, Aubrey L; Boatwright, Christina A; Lee, Junsu; Atkins, Alisa; Tijhuis, Andrea; Spierings, Diana CJ; Bazzi, Hisham; Foijer, Floris; Jordan, Philip W; Stracker, Travis H; Holland, Andrew J
Abstract: Mutations in centrosome genes deplete neural progenitor cells (NPCs) during brain development, causing microcephaly. While NPC attrition is linked to TP53‐mediated cell death in several microcephaly models, how TP53 is activated remains unclear. In cultured cells, mitotic delays resulting from centrosome loss prevent the growth of unfit daughter cells by activating a pathway involving 53BP1, USP28, and TP53, termed the mitotic surveillance pathway. Whether this pathway is active in the developing brain is unknown. Here, we show that the depletion of centrosome proteins in NPCs prolongs mitosis and increases TP53‐mediated apoptosis. Cell death after a delayed mitosis was rescued by inactivation of the mitotic surveillance pathway. Moreover, 53BP1 or USP28 deletion restored NPC proliferation and brain size without correcting the upstream centrosome defects or extended mitosis. By contrast, microcephaly caused by the loss of the non‐centrosomal protein SMC5 is also TP53‐dependent but is not rescued by loss of 53BP1 or USP28. Thus, we propose that mutations in centrosome genes cause microcephaly by delaying mitosis and pathologically activating the mitotic surveillance pathway in the developing brain. Synopsis: How centrosomal mutations cause microcephaly in humans and mice has remained unclear. Here, a mechanism that delays mitosis upon centrosomal loss in cultured cells is found to also mediate the in vivo consequences for developing mouse brains in such context, but not in centrosome‐independent microcephaly conditions. Neural Progenitor Cell (NPC) depletion is linked to TP53‐mediated cell death in several microcephaly models. In mouse models with mutations in centrosomal genes, depletion of centrosome proteins in NPCs prolongs mitosis and increases TP53‐mediated apoptosis in the progeny. Cell death after a delayed mitosis can be rescued by inactivation of the 53BP1‐USP28‐TP53 mitotic surveillance pathway, without correcting the upstream centrosome defects or extended mitosis. Microcephaly caused by the loss of the non‐centrosomal protein SMC5 is also TP53‐dependent, but not rescued by ablation of the mitotic surveillance pathway. Abstract : A mechanism that delays mitosis upon centrosomal loss in cultured cells appears to also underlie the in vivo consequences for brain size and neural progenitor proliferation in developing mouse brains.